Tom Clancy True faith and allegiance - Greaney, Mark; Clancy, Tom, 1947-2013 (Jack Ryan and John Clark novel, 2016)
It begins with a family dinner in Princeton, New Jersey. After months at sea, U.S. Navy Commander Scott Hagan, captain of the USS James Greer, is on leave when he is attacked by an armed man in a crowded restaurant. Hagan is shot, but he manages to fight off the attacker. Though severely wounded, the gunman reveals he is a Russian whose brother was killed when his submarine was destroyed by Commander Hagan's ship. Hagan demands to know how the would-be assassin knew his exact location, but the man dies before he says more. As more deadly events involving American military and intelligence personnel follow, all over the globe, it becomes clear that there has been some kind of massive information breach and that a wide array of America's most dangerous enemies have made a weapon of the stolen data. With U.S. intelligence agencies potentially compromised, it's up to John Clark and the rest of The Campus to track the leak to its source.